An exploratory analysis of urinary organophosphate ester metabolites and oxidative stress among pregnant women in Puerto Rico - Ingle, Mary E. (Sci Total Environ, 2019)
BACKGROUND: Organophosphate esters (OPEs) are used as flame retardants and plasticizers. Oxidative stress, the imbalance of reactive oxygen species and antioxidants, measured prenatally has been associated with adverse birth outcomes including preeclampsia and preterm birth. We are the first study to investigate the relationship between OPEs and oxidative stress among pregnant women. METHODS: Pregnant women 18–40 yrs. were recruited in Northern Puerto Rico (n=47) between 2011 and 2015. OPE concentrations of: bis(2-chloroethyl) phosphate (BCEtP), bis(1-chloro-2-propyl) phosphate (BCPP), bis(1,3-dichloro-2-propyl) phosphate (BDCPP), dibutyl phosphate (DNBP), and diphenyl phosphate (DPHP) and biomarkers for oxidative stress, 8-hydroxy-2′-deoxyguanosine (8-OHdG) and 8-isoprostane were measured in urine up to three times during pregnancy. Associations between oxidative stress biomarkers and OPEs were assessed using linear mixed models adjusted for specific gravity, age, BMI, and income. RESULTS: Metabolites BCEtP, BDCPP, and DPHP were frequently detected (>97%). OPE metabolite concentrations remained stable over time (Intraclass correlation coefficients (ICCs): 0.51–0.60). Metabolites BCEtP, BCPP, and DPHP were associated with an increase in 8-isoprostane and OHdG. An interquartile range (IQR) increase in BDCPP was associated with a 21% increase in 8-isoprostane (p<0.01), while and IQR increase in DPHP and BCPP was associated with a 12% increase (p=0.04, p=0.08, respectively). IQR increases in BDCPP and DPHP were also associated with an 18 and 19% increase in OHdG, respectively (p<0.01). CONCLUSION: OPE metabolites were frequently detected and our results suggest that exposure to OPEs is associated with higher levels of oxidative stress. Further investigation into these relationships and birth outcomes is warranted.